KEBIJAKAN PENANGGULANGAN KEJAHATAN TERHADAP PELAKU KELAINAN SEKSUAL YANG MELAKUKAN PENCABULAN MELALUI REHABILITASI - Krismiyarsi Krismiyarsi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
Criminal acts of sexual abuse under Article 82 of Law Protection of children, also under Article 292 of the Criminal Code, as general criminal law where criminal threats 5 years imprisonment, against the actions of sufficient age, who do obscene acts with other people the same sex, which known or reasonably should be expected, that was not old enough. These acts of abuse against people want castrated using chemicals. This paper provides an alternative in criminal policy for perpetrators of sexual disorder which criminal act of abuse by using medic rehabilitation and social rehabilitation, in Psychiatric Hospital or Psychiatric Therapy, considering the criminal act of abuse committed by perpetrators of sexual disorders like people whose souls disturbed because of illness, so that Article 44 can apply to cases.